2021
DOI: 10.1186/s13023-021-02106-7
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and current shortcomings in the cooperation between German centers for rare diseases and primary care physicians: results from the project TRANSLATE-NAMSE

Abstract: Background The TRANSLATE-NAMSE project with the strengthening of the centers for rare diseases with their affiliation to the European Reference Networks was a major step towards the implementation of the German National Plan of Action for People with Rare Diseases establishing better care structures. As primary care physicians, general practitioners and pediatricians play a central role in the diagnosis of patients with rare disease, as it is usually them referring to specialists and rare disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
3
Order By: Relevance
“…Based on our data this was not a surprise because most rare disease associations do not use a strategic communication plan and in fact, most associations are not focused on fundraising. In multiple analyses, authors concluded that there is discordance between the medical and patient communities; in other words, there is not a common language with which to communicate (30)(31)(32)(33). This too is not a surprise because strategic focus is generally used by rare disease associations often because funds are not available to support professional communication plans.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data this was not a surprise because most rare disease associations do not use a strategic communication plan and in fact, most associations are not focused on fundraising. In multiple analyses, authors concluded that there is discordance between the medical and patient communities; in other words, there is not a common language with which to communicate (30)(31)(32)(33). This too is not a surprise because strategic focus is generally used by rare disease associations often because funds are not available to support professional communication plans.…”
Section: Discussionmentioning
confidence: 99%
“…B. Zentrenstruktur) kennen. Eine aktuelle Studie zeigt, dass dies nicht vorausgesetzt werden kann [ 39 ]. Vor diesem Hintergrund sind Konzepte zur Bekanntmachung der Strukturen und zur Sensibilisierung der Primärversorgenden für Seltene Erkrankungen eine wichtige Ergänzung.…”
Section: Diskussionunclassified
“…Dieses Versorgungsprojekt "TRANS-LATE-NAMSE" wurde von April 2017 bis September 2020 durch den Innovationsfond des G-BA für neue Versorgungsformen in der gesetzlichen Krankenversicherung gefördert [9][10][11] Definierte SE wurden zunächst entsprechend der aktuellen Leitlinien der AWMF diagnostiziert, dazu gehörten angeborene Stoffwechselerkrankungen und Hypothyreose, adrenogenitales Syndrom (oder klinisch diagnostizierte Störungen der Geschlechtsentwicklung), primäre Immundefekte, Autoinflammationserkrankungen oder seltene Hämoglobinopathien. Anschließend wurden diese Patienten mittels der im Projekt entwickelten multiprofessionellen Versorgungspfade entsprechend den aktuellen Leitlinien betreut.…”
Section: Translate-namseunclassified
“…Dieses Versorgungsprojekt „TRANSLATE-NAMSE“ wurde von April 2017 bis September 2020 durch den Innovationsfond des G‑BA für neue Versorgungsformen in der gesetzlichen Krankenversicherung gefördert [ 9 – 11 ]. Daran nahmen neben 9 universitären Zentren für SE 2 Krankenkassen (AOK Nordost und Barmer GEK) und die Allianz chronischer seltener Erkrankungen (ACHSE e. V.) teil.…”
Section: Translate-namseunclassified